The hidden homeownership welfare state: An international long-term perspective on the tax treatment of homeowners - Konstantin A. Kholodilin; Sebastian Kohl; Artem Korzhenevych; Linus Pfeiffer (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
Welfare is traditionally understood through social security decommodifying labor markets or social investment policies. In the domain of housing, however, welfare for homeowners is largely hidden in the tax codes' fiscal exemptions. Based on a content analysis of legislation, this paper introduces a novel yearly database of 37 countries between 1910 and 2020 to uncover the 'hidden welfare state' of taxes on imputed rent, deductibility of mortgage payments, housing capital gains tax and VAT on newly built dwellings. Summary indices of homeownership attractiveness and neutrality of the tax code show that fiscal homeownership policies have been in decline until the 1980s and risen ever since. They are in place where finance is liberally and labor restrictively regulated. Contrary to the classical welfare state, they are not associated with an economic logic of industrialism or left-wing governments, but a rent-regulation alternative of Common-Law jurisdictions and smaller countries. As welfare for property owners, the logic of fiscal homeownership welfare diverges from the classical welfare for the laboring classes.
Keywords: C43; H24; K25; R38; 330; homeownership taxation attractiveness; tenure neutrality; leximetrics; international longitudinal data